Meningkatkan Kemampuan Mengenal Bentuk Geometri Melalui Permainan Cacaburange - Ayu Fajarwati; Wulan (PEDAGOGIKA, 2020)
The Purpose of this research is to improve ability of geometry through cacaburange games. This research was implemented at Setiabudhi Kindergarten, Rangkasbitung in July-August 2018/2019. The method used is action research through two cycles, the cycles consist of planning, acting, observing, and reflecting. Subjects were children ages 4-5 years at TK Setiabudhi who had problems in ability of geometry as many as 10 people. Data collecting using observation sheets, field notes, and record documentation. Analysis of the percentage of data used in this study based on Mills in the amount of 71%, the end result of overall analysis is 84,66% with increased 46,11%. Based on the increasing percentage of the current study, it can be stated that the hypothesis is accepted. It can be concluded that the use of cacaburange games can improve ability of geometry on children ages 4-5 years. The implications of this research that the cacaburange games can be used as an alternative to improve the ability of geometry. Increased ability of geometry in children can help with the child’s ability to understand and recognize geometry.